Using medical exome sequencing to identify the causes of neurodevelopmental disorders: Experience of 2 clinical units and 216 patients. Issue 3 (4th October 2017) - Chérot, E.; Keren, B.; Dubourg, C.; Carré, W.; Fradin, M.; Lavillaureix, A.; Afenjar, A.; Burglen, L.; Whalen, S.; Charles, P.; Marey, I.; Heide, S.; et al.
Abstract : Although whole‐exome sequencing (WES) is the gold standard for the diagnosis of neurodevelopmental disorders (NDDs), it remains expensive for some genetic centers. Commercialized panels comprising all OMIM‐referenced genes called "medical exome" (ME) constitute an alternative strategy to WES, but its efficiency is poorly known. In this study, we report the experience of 2 clinical genetic centers using ME for diagnosis of NDDs. We recruited 216 consecutive index patients with NDDs in 2 French genetic centers, corresponded to the daily practice of the units and included non‐syndromic intellectual disability (NSID, n = 33), syndromic ID (NSID = 122), pediatric neurodegenerative disorders ( n = 7) and autism spectrum disorder (ASD, n = 54). We sequenced samples from probands and their parents (when available) with the Illumina TruSight One sequencing kit. We found pathogenic or likely pathogenic variants in 56 index patients, for a global diagnostic yield of 25.9%. The diagnosis yield was higher in patients with ID as the main diagnosis (32%) than in patients with ASD (3.7%). Our results suggest that the use of ME is a valuable strategy for patients with ID when WES cannot be used as a routine diagnosis tool. Abstract : TruSight One global diagnostic yield in 216 consecutive patients with neurodevelopmental disorder, negative for X fragile and chromosomal microarray from 2 French clinical genetic centers (25.9%).